DEVELOPMENT OF THE THAI EXERCISE ADDICTION INVENTORY - Mattayakorn, Korada (Academic Journal of Thailand National Sports University, 2019)
Nowadays, people are more interested in studying harmful effects of excessive exercise, also known as exercise addiction. In Thailand, not many studies have been conducted on this issue and no compulsive exercise test for Thai people has been found. The aim of the present study was to develop a Thai Exercise Addiction Inventory (TEAI) and to find out its validity and reliability. The TEAI was developed based on the original 6-item EAI of (Terry, Szaboo, & Griffiths, 2004). The Exercise Addiction Inventory was translated into Thai and back translated (Brislin, 1987) by experts in exercise and sports psychology, and English language specialists. The TEAI was pilot tested with 30 exercisers whose exercise behaviors were similar to the subjects. The reliability of the TEAI determined with Cronbach’s alpha was 0.75. The subjects selected through purposive sampling were 190 people (157 males and 33 females) in the age range 20-70 years living in Songkhla Province, Thailand who exercised by cycling, walking and running. The results of construct validate analysis and confirmatory factor analysis (CFA) showed that the model aligned with the empirical data (c2 = 12.24, df = 9, GFI = 0.97, AGFI = 0.95, CFI = 0.98, NNFI = 0.97, NFI = 0.95 and RMSEA = 0.04). It can be concluded that the Thai Exercise Addiction Inventory (TEAI) is a valid and reliable instrument for use in assessing exercise addiction of Thai people.